Hexamermis paranaense new species (Nematoda, Mermithidae): A parasite of Diloboderus abderus (Coleoptera, Scarabaeidae) in Argentina - Achinelly, María Fernanda (2008)
A new species, Hexamermis paranaense n. sp. (Nematoda, Mermithidae), a parasite of larvae of Diloboderus abderus Sturm, 1826 (Coleoptera, Scarabaeidae) is described and illustrated. This new species is characterized by amphids small, amphidial opening pocket-shaped, the anterior portion of the vagina muscularized and slightly protruding with a descending branch forming a loop before joining the uterus, and three rows of genital papillae: the ventrolateral divided in two rows with eight papillae in the outer row and with six papillae in the inner one; the ventral row with four pairs and one single preanal papillae, and with two pairs, a triplete, one pair, a single and one pair postanal papillae.